Study and assessment specific characteristic divorced families - Safari L (Iran University of Medical Sciences, 1988)
EXTRACTIn any era to the present era, Risk of Changes of family and their adverse effects are not studied and also these adverse effects are now more than any time. Statistics show that each year the number of divorce will increase and there is the risk for many families. So, after the Second World War II the rate of divorce is not lower from average of 400,000 cases. The result of research in England showed that the rate of divorce in 1985 will be 22,ooo and in 1978 will be 45,000. Egypt has the highest rate of divorce among Muslim countries and there is an exaggerated Statistics about it. For example, according to Amozeghar (1355) there is 3 divorce for every 4 marriage. In the village which entertainment and lust is lower than the city, there is 1 divorce for every 4 marriage.